Density, dynamic viscosity, and electrical conductivity of two hydrophobic functionalized ionic liquids. (November 2015) - Liu, Qing-Shan; Liu, Jing; Liu, Xiao-Xia; Zhang, Shi-Tao
Highlights: Targets of this research are functional hydrophobic ionic liquids. Density, dynamic viscosity and electrical conductivity were determined. Influences of functional group to properties were discussed. Relationship of ρ, η and σ were described systematically. Abstract: Two of hydrophobic functionalized ionic liquids (FILs) were synthesized according to the traditional method. The FILs are 1-(cyanomethyl)-3-methylimidazolium bis[(trifluoromethyl)sulfonyl]imide ([MCNMIM][NTf2 ]) and 1-(2-hydroxyethyl)-3-methylimidazolium bis[(trifluoromethyl)sulfonyl]imide ([EOHMIM][NTf2 ]). Density, dynamic viscosity, and electrical conductivity of the two FILs were determined in the range of T = (283.15 to 353.15) K. The other important physico-chemical properties, like molecular volume, standard molar entropy, and lattice energy, of the two FILs were estimated by empirical equations on the bases of the experimental density. The Vogel–Fulcher–Tamman (VFT) and Arrhenius equations were used for fitting of the temperature dependence of the dynamic viscosity and electrical conductivity. The activation of electrical conductivity and dynamic viscosity were calculated by the final version VFT equation. The molar conductivities were determined from density and electrical conductivity by the empirical equation. According to Walden rule, the Walden equation was used for description of the density, dynamic viscosity, and electrical conductivity. The introduction of the functional group (cyano and hydroxy) on imidazolium ring can provided hydrogen bond formation. The FILs exhibited the higher density, dynamic viscosity and lower electrical conductivity than traditional non-functional ILs.